Textbook of biochemistry : (Wiley-Liss, 2006)
Thomas M. Devlin's Textbook of Biochemistry with Clinical Correlations presents the biochemistry of mammalian cells, relates events at a cellular level to the subsequent physiological processes in the whole animal, and cites examples of human diseases derived from aberrant biochemical processes. The organization and content are tied together to provide students with the complete picture of biochemistry and how it relates to humans. Loaded with new material and chapters and brimming with detailed, full-color illustrations that clearly explain associated concepts, this sixth edition is an indispensable tool for students and professionals in the medical or health sciences.